ROLE OF GEOMETRY OPTIMIZATION IN ENHANCING THE EFFICIENCY OF AIR-PURIFICATION DEVICES - Djurayev Sherzod Sobirjonovich (Web of Journals Publishing, 2025)
Geometry is the single most influential design variable in high-efficiency air-purification devices such as cyclone and multicyclone separators. Over the last five years, advances in computational fluid dynamics (CFD) and surrogate-based multi-objective optimisation have enabled designers to lower pressure drop by 20–40 % while simultaneously raising fine-particle collection by up to 15 % without adding moving parts.
Keywords: Cyclone separator; multicyclone; CFD; surrogate modelling; Pareto optimisation; pressure drop; particle collection; vortex finder; cone angle; air pollution control; energy efficiency; digital twin; scale-up; erosion; PM 2.5.